Morphodynamic Cartography Visualization of Wulan River Estuary Systems from Space to Numerical Approach Based on Multi-Season Analysis - Khakhim, Nurul; Kurniawan, Agung; Pranowo, Widodo Setiyo (Geomatics and Environmental Engineering, 2024)
This research aims to investigate the morphodynamics of the Wulan River estuary in Demak Regency using the integration of multispectral remote sensing images and numerical modeling. In this study, PlanetScope for a manualvisual analysis of estuary morphodynamics and Sentinel-2 MSI Level 2A to obtain periodic total suspended solids (TSS) information for the east and west monsoon seasons. MIKE by DHI software used to develop hydrodynamic numerical modeling in order to characterize the current circulation and sediment transport model. Based on a marine cartography aspect, the obtained results illustrated that the climatological phenomenon of seasonal forcing plays a role in the development of the current circulation and indirectly influences the sediment transport. During the west season, the morphodynamics in the Wulan River estuary are much more massive and significant as compared to the east season. A projection of the deposition that results from the sediment transport is described in the bed-thickness change; this occurs in the western part of the Wulan River estuary during the east season, while the bed-thickness change occurs predominantly in the northern part during the west season (where there was previously a beach sandbar phenomenon). This was verified through multi-temporal satellite imagery that the deposition that occurs in the northern part of the Wulan River estuary during the west season is increasingly progressive and massive.